Historic drought in northern Kenya shifts diet and mobility away from traditional pastoralism as resource security and nutrition falter - Asher Y. Rosinger; Matthew Douglass; Amanda McGrosky; Kedir Teji Roba; Benjamin Davies; Natalie Meriwether; Alfredo J. Rojas; Leslie Ford; Hannah Jacobson; Faith Wambua; Elena Hinz; Srishti Sadhir; et al. (Global Environmental Change, 2026)

Human energy expenditure and thermoregulation during persistence hunting in the Namib - Martin Hora; Robi Dattatreya; Michal Struška; Herman Pontzer; Vladimír Sládek (Journal of Human Evolution, 2025)

Corrigendum to “The effect of bi-iliac breadth on core body temperature” [J. Hum. Evol. 195 (2024) 103580] - Jennifer Eyre; Scott A. Williams; Mark Grabowski; Sandra Winters; Herman Pontzer (Journal of Human Evolution, 2024)

The effect of bi-iliac breadth on core body temperature - Jennifer Eyre; Scott A. Williams; Mark Grabowski; Sandra Winters; Herman Pontzer (Journal of Human Evolution, 2024)

Urban eastern gray squirrels (sciurus carolinensis) show little seasonal variation in biochemical and hematological parameters - Rebecca Rimbach; Olivia A. Petritz; Julie A. Balko; Herman Pontzer (Urban Ecosystems, 2024)
Urban wildlife faces unique physiological and behavioral challenges compared to conspecifics which live in less altered natural habitats. Animals in urban habitats are also exposed to urban stressors and commonly make use of inappropriate food sources from trash bins and dumpsters, which may affect their heath status. The goals of this study were to evaluate overall health of an urban population of eastern gray squirrels ( Sciurus carolinensis ) and to assess seasonal changes in several health parameters. Squirrels ( N = 45) were trapped in Durham, North Carolina, USA and briefly anesthetized with inhalant anesthetic for physical examination, body mass collection, and venipuncture via the femoral vein. Collected blood was analyzed for several health parameters via hematology and biochemistry analyses including assessment of lipids and kidney and liver values. Physical examinations were clinically unremarkable and similar across seasons. Females had higher cholesterol values and lower creatinine values compared to males. Seasonal differences occurred in few parameters and were detected only between summer and either fall or spring. Potassium and monocytes were higher in summer compared to spring, and creatinine, BUN and monocytes were higher in summer compared to fall. Overall, health parameters of urban eastern gray squirrels fell within published reference ranges for the species. Together, these results suggest that urban squirrels in this study population can maintain good health in an anthropogenic habitat.

Gray squirrels consume anthropogenic food waste most often during winter - Rebecca Rimbach; Gabrielle Butler; Pratik R. Gupte; Jörg Jäger; Claire Parker; Herman Pontzer (Mammalian Biology, 2023)

Ontogeny of Ranging in Wild Chimpanzees - Herman Pontzer; Richard W. Wrangham (International Journal of Primatology, 2006)